The role of the Ministry of Defense in the process of integration and regulation of Military Communications in Brazil - Chaves, Rodrigo Silva (Law, State and Telecommunications Review, 2014)
Purpose ”“ The purpose of this article is to introduce the reader to the technical and political context whereupon are inserted the Military Communications in Brazil, evidencing the regulatory and integrative role currently played by the Ministry of Defense. Methodology/approach/design ”“ This research makes predominant use of descriptive and comparative techniques, in order to inform the reader on the subject highlighted. Findings ”“ The article concludes with the need for rationalization and unification of national policy for Military Communications, as determinant for the effective integration of the Armed Forces in joint operations. Practical implications ”“ The article highlights the benefits that standardization of technical requirements by the Ministry of Defense may bring in terms of reducing the cost of purchasing and maintaining equipment and military communications systems, by way of enhancing economies of scale, effectiveness and operational efficiency in the joint operations of the Armed Forces. Originality/value ”“ This article addresses a branch of knowledge rarely assessed by academic researchers in Brazil having thus pioneering role in contributing to issues related to National Defense as Military Communications are discussed by civil society.